The effects of Rhodopseudomonas palustris on the improvement of agronomic traits and key enzyme-coding genes related to polysaccharide biosynthesis in Codonopsis pilosula - Wanhua Wang; Shuhui Gao; Yi Sun; Hong Yang; Jinlong Li; Jing Li; Xianhui Zheng; Guane Yang (PLoS ONE, 2025)
The content of Codonopsis pilosula polysaccharide (CPPS) is a critical indicator of the quality and quantity of Codonopsis pilosula (C. pilosula), though the biosynthetic mechanism of CPPS accumulation through the application of Rhodopseudomonas palustris (R. palustris) remains unclear. Therefore, when planting C. pilosula, we applied R. palustris through spraying and root irrigation (10 ml), and harvested its fresh roots, stems and leaves as experimental materials. Agronomic traits and CPPS content were determined, while transcriptome sequencing was analyzed, with gene expression verified by fluorescence quantitative PCR. The results revealed that the phenotype of C. pilosula was improved, and the content of CPPS in roots, stems, and leaves increased by 90.22%, 61.11%, and 20.00%, respectively. Following sequencing, 10,880, 8,578, and 12,340 differentially expressed genes (DEGs) were identified in response to R. palustris application. The DEGs in each tissue were primarily enriched in starch and sucrose metabolism, phenylpropanoid and flavonoid biosynthesis, glycolysis/gluconeogenesis, MAPK signaling pathways, and plant hormone signal transduction. A total of 12 genes encoding sucrose synthase (SUS), hexokinase (HK), β-fructofuranosidase (sacA), and fructokinase (scrK) were significantly upregulated in the tissues, with expression levels higher in roots than in stems and leaves. Additionally, 10 genes encoding proteins with jasmonate ZIM domains (JAZ), coronatine-insensitive protein 1 (COI1), and transcription factor MYC2 (MYC2) may be closely associated with the improvement of agronomic traits in C. pilosula. This study demonstrated that C. pilosula’s response to exogenous R. palustris induced the activation of SUS, HK, sacA, scrK, JAZ, COI1, and MYC2 activities. The upregulation of genes regulating these enzymes contributed to the increased CPPS content and the enhancement of agronomic traits in C. pilosula. These findings provide a reference for cultivating high-quality C. pilosula at the molecular level.